The impact of digital transformation on the financial performance of listed F&B companies in Vietnam - Dam, Thi Thanh Huyen; Dam, Tu Thanh; Dang, Thi Minh Nguyet; Nguyen, Thi Thu Hang (International Journal of Innovative Research and Scientific Studies, 2025)
Amid the rapid global digital transformation, the food and beverage (F&B) industry in Vietnam is also partaking in this trend. Digital transformation has become a decisive factor, not only helping enterprises in this sector optimize their operational processes but also enhancing customer experience and promoting sustainable growth. This research aims to analyze the impact of digital transformation on the financial performance of listed F&B companies on the Vietnam stock market. Data was collected from two sources: (i) financial reports; and (ii) surveys on the level of digital transformation at listed F&B companies. The research results show that digital transformation negatively affects the financial performance of listed F&B companies. Additionally, financial performance is also influenced by the scale of assets, financial leverage, current payment ratio, and bankruptcy risk. These results are consistent with the reality in Vietnam, as this is the period when businesses start to undergo digital transformation. This is when businesses significantly require capital without experience; hence, the effectiveness of digital transformation investment has not yet been observed. From the research results, the authors propose implications for digital transformation to help increase financial performance for listed F&B companies in Vietnam.